Analisis Feminisme pada Novel "Dia Aurora" Karya Nurwina Sari - Tenriana, Nuzul; Iriany, Rosary; Aristoteles, Ferdinandus; Muhdar, Andi; Jumriati, Jumriati (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to reveal religious and cultural views on the dignity of women who tend to have feminine traits and their relation to the main character in the novel 'Dia Aurora' by Nurwina Sari. Furthermore, it aims to describe the main character’s struggle in obtaining her rights and to examine the gender perspectives through feminist literary theory. This research applies a qualitative case study approach using documentation techniques. The findings indicate the dominance of patriarchal culture that affects the female protagonist. The novel also reflects women’s struggles in asserting their rights based on the Indonesian Constitution. This study is expected to provide insights into gender inequality and the importance of equal rights for women.